A new unequal clustering protocol with local re-clustering mechanism for wireless sensor networks. (2016) - Tang, Hao; Hong, Wei; Zhou, Lei; Miao, Gangzhong
A new unequal clustering protocol with local re-clustering mechanism is proposed to mitigate the 'hot spot' problem and thereby prolong the network lifetime of a wireless sensor network (WSN). In the setup phase, the network is partitioned into several unequal-size layers based on the minimum hop count of each node to the base station (BS). Then each layer is further partitioned into several layer-dependent-size clusters by a weight-based cluster head (CH) competition, where candidate nodes participating in CH election are selected by the BS with a new exploration approach. In addition, we propose a local re-clustering mechanism to further mitigate the uneven energy load during the data transmission phase, that is, different layers reselect their CHs at different frequencies according to their relative distances to the BS. Furthermore, for local re-clustering, a simplified CH rotation approach is proposed to lessen the communication and computation overhead. The simulation results demonstrate that our proposed protocol is effective in prolonging the network lifetime and in balancing the energy consumption.